P-141 The good, the bad and the ugly – The fate of collapsed blastocysts in frozen embryo transfer. (30th June 2022) - Serrano Comes, C; Pastor Leary, C; Hörmann-Kröpfl, M; Schenk, M; Weiss, G
Abstract: Study question: What is the clinical outcome of collapsed blastocysts without signals of re-expansion in frozen embryo transfers (FET)? Summary answer: FET of non-re-expanded blastocysts after thawing showed a live-birth rate in 11.5% of the cases. Embryos vitrified on day 5 revealed the best results. What is known already: Embryo viability is crucial for FET to be successful. Since the introduction of vitrification techniques, outcomes have improved substantially and are even comparable to fresh transfers. Nevertheless, some indicators may help predict the outcome of frozen-thawed blastocysts. Blastocoele re-expansion after thawing has been widely studied and is a strong predictor of clinical pregnancy outcome. However, accurate data on non-re-expanded blastocysts after FET is still not available. Hence, this study aims to evaluate the clinical outcome of non-re-expanded blastocyst after FET. Study design, size, duration: The retrospective study was designed and conducted at the Kinderwunsch Institut Schenk GmbH (Dobl, Austria). Data was collected from FET performed between 2017 and 2021. In total, 104 FET cycles of collapsed blastocysts were analysed. All the transfers performed were single embryo transfers (SET). Patient's average age was of 33.6 years at the time of embryo vitrification. Embryos were excluded if they showed more fragmentation than before vitrification. Participants/materials, setting, methods: Patients were divided into two groups following the time of blastocyst cryopreservation: day 5 (44 SET) and day 6 (60 SET); which was dependant on the time of blastocoel expansion. They were further divided according to the trophectoderm quality: good (42 SET) and poor (62 SET) and the overall embryo quality, considering trophectoderm and inner cell mass (ICM): good (37 SET) and poor (67 SET). In both cases quality was assessed before vitrification. Main results and the role of chance: A total of 104 collapsed blastocysts were transferred (SET). 16.3% of the patients had a positive biochemical pregnancy. 11.5% of the pregnancies resulted in a live birth and 4.8% of the pregnancies ended in abortion. FET with day 5 non-re-expanded blastocysts after thawing showed better results than day 6 thawed blastocysts regarding biochemical pregnancy (29.5% vs 6.6%, p = 0.02) and live birth rate (20.4% vs 5%, p = 0.017). Good embryo quality before vitrification showed a trend for better clinical outcome, however, results were not significant. A good trophectoderm quality before vitrification revealed a live birth rate of 16.7% compared to 8.1% in poor trophectoderm quality. Regarding overall embryo quality (trophectoderm and ICM quality) the results were 14.3% deliveries for good quality blastocysts vs 7.6% for poor quality blastocysts. Limitations, reasons for caution: The sample size may be seen as a study limitation. However, statistically significant results were obtained. Nonetheless, results should be confirmed with a bigger sample size. Wider implications of the findings: The present study revealed a lower chance of live birth for non-re-expanded blastocysts after thawing, which should nevertheless not be overlooked; specially in cases with good quality embryos frozen and thawed on day 5. Transfer of collapsed embryos after thawing would be recommended taking into consideration the study results. Trial registration number: Not Applicable